Popular education, alternative pedagogies, and systematization of exp eriences. history and horizons - Gómez Sollano, Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In order to think the field of popular education, this article aims to recover some of the historical and conceptual references developed in the program “Pedagogical alternatives and planning education in Latin America” (Known by its Spanish acronym, APPEAL). Likewise, it is analyzed the potential that allows the systematization of in-process and no-documented experiences, as well as the study of the experiences already collected, since they reflect somehow the problem, its dimensions and alternative trends in a particular region, and point out possible challenges and limitations in pedagogical action and transformation. This work is organized in three main sections to develop the following topics: an approaching to the term popular education, the importance of the pedagogical experiences’ systematization and debates on this subject, and new horizons to keep thinking the field of popular education up. In each section different levels of analysis are discussed to place the historical formation of the popular education concept, the production of alternative pedagogical experiences, its systematization and the implications for thinking its current reconfiguration and emergency in Latin America, particularly.